The duty of care principle / Norizan Abdul Rahman - Abdul Rahman, Norizan (Faculty of Law, 1986)
This paper deals with the duty of care principle with special reference 'to its extension and application in United Kingdom and Malaysia. Negligence is the omission to do something which a reasonable man, guided upon those considerations which ordinarily regulate the conduct of human affairs, would do,or doing something which a prudent and reasonable man would not do. The law of toirfcs especially on duty of care principle is "a based on judicial decisions and there is no statutory law in this area. Therefore the discussions is centred primarily on cases, Reception of English decisions is by virtue of Section 3 of the Civil Law Act, 1956 (revised 1972).